United States hydrographic surveys in Canadian western Arctic, 1955–57 (Polar Record, 1959)
As a result of these operations 1000 miles of a deep-water North West Passage were charted. In addition, five hundred square miles of detailed hydrographic survey were made in the most dangerous areas. About 285 miles of coastline were covered by triangulation and 28 radar reflector towers were built as navigational aids. The results of the surveys were published in a series of 33 charts and in greatly improved sailing directions.